PERLINDUNGAN HUKUM KEPENTINGAN ANAK DI BAWAH UMUR TERHADAP HIBAH YANG MELANGGAR LEGITIEME PORTIE - NITA NILAN SRY REZKI PULUNGAN (PREMISE LAW JURNAL, 2015)
In practice, the grant giver always grants his/her property to the grant recipient with the greater amount than the part available in the property to be granted or in fact a part of the grant received by the grant recepient absolutely belongs to the legitimaries heirs that the dispute of inheritance occurs among the heirs. To prove whether or not the grant given by the grant giver has violated the legitieme portie, and does not inform the total amount of all boedel of the inheritance. The attempt to protect thr ight to inherite of the underage heirs in terms of granting by the grant giver violating the legitieme portie is that it is a must to obtain a decision in relation to the transfer of the property of the underage from the court of law, the existence of representative instution towards the legal action for the property of the underage, the action of control or monitoring the property containing the right of the underage heirs with the condition that transferring the property owned by the underage heirs that should be allowed get license from the court of law in order to prevent the violation that might be done by the guardian of the underage heirs or other parties who can inflict loss to the underage heirs. Keywords: Legal Protection, Legitieme Portie, Underage Heir